The use of 18f-fluorodeoxyglucose positron emission tomography to assess clinical outcomes of patients wıth borderline resectable pancreatic cancer - Durmuş, Ali; Yılmaz, Ahmet; Malya, Fatma Ümit; Öztürk, Gökmen; Bektaşo?lu, Hüseyin Kazım; Ertuğrul, G.; Karyağar Sağlampınar, Sevda; Karatepe, O?uzhan (Georgian Association of Business Press, 2016)
The aim of this study is to evaluate the effect of 18FDG PET on preoperative staging and clinical management of pancreatic cancer. Between December 2011 and February 2015, 28 consecutive patients with borderline resectable pancreatic cancer were evaluated with both 18FDG PET scans and conventional preoperative imaging studies. Medical records of all patients were noted prospectively. 18FDG PET findings were compared with conventional imaging studies and over-staging or down-staging rates with changes in clinical management were evaluated. The correlation of 18FDG PET with conventional imaging studies was evaluated with a kappa agreement coefficient. A number of 22 (78.5%) patients had pancreatic head cancer and 6 (21.4%) patients had pancreatic body and tail cancers. Based on 18FDG PET, additional lesions were found in 4 (14.28%) of the patients which were lung and peritoneal lesions as metastasis. No hepatic metastasis or supraclavicular lymph node involvement was confirmed in patients. Routine use of 18FDG PET for preoperative staging has not an effect on cancer management in 96.8% of our patients. In conclusion, 18FDG PET has additional value over conventional radiologic techniques for monitoring the treatment response in locally advanced pancreatic cancer patients. It is feasible to predict early metastasis and patient outcome early (after one course of IC) during therapy.
Keywords: Fluorodeoxyglucose; Tomography; Pancreatic Cancer